2010
DOI: 10.1007/s10152-009-0186-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of gastropod fauna on subtidal sandy sediments of the Ensenada de Baiona (NW Iberian Peninsula)

Abstract: The temporal variation of the gastropod fauna inhabiting sandy sediments of the Ensenada de Baiona (Galicia, Spain) was studied at three subtidal sites from February 1996 to February 1997 by means of quantitative sampling. A total of 5,463 individuals representing 51 gastropod species and 22 families were found. The family Pyramidellidae was the most diverse in number of species (11 species), followed by Rissoidae and Trochidae (4 species each). The dogwhelk, Nassarius reticulatus, and the rissoid snail, Risso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…The temporal variations observed within Coombabah Lake, however, are in contrast to those recorded in some other studies within Australian intertidal systems that reported no significant seasonal trends (Dittman, 2002;Jones, Watson-Russell, and Murray, 1986;Rainer, 1981). In many cases, intra-annual trends in macrofauna dynamics are attributable to patterns of species recruitment, water column and sediment conditions, competition, and predation stresses (Moreira, Aldea, and Troncoso, 2010). These facts could help explain the lower Predation is most often presumed to be an important organising force of soft-sediment community structures (Bell, 1980;Brey, 1991).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The temporal variations observed within Coombabah Lake, however, are in contrast to those recorded in some other studies within Australian intertidal systems that reported no significant seasonal trends (Dittman, 2002;Jones, Watson-Russell, and Murray, 1986;Rainer, 1981). In many cases, intra-annual trends in macrofauna dynamics are attributable to patterns of species recruitment, water column and sediment conditions, competition, and predation stresses (Moreira, Aldea, and Troncoso, 2010). These facts could help explain the lower Predation is most often presumed to be an important organising force of soft-sediment community structures (Bell, 1980;Brey, 1991).…”
Section: Discussioncontrasting
confidence: 81%
“…Consequently, estuarine sediments often support high abundances and biomasses of benthic macrofauna (Moreira, Aldea, and Troncoso, 2010;Snelgrove, 1999), which provide vital food for many crustacean, fish, and shorebird species (Wolff, 1987;Ysebaert et al, 2005). As a result, intertidal habitats are of high conservation value (Fujii, 2007;Kennish, 2002) and often function as nursery grounds for important recreational and commercial fish species (Gray, McElligott, and Chick, 1996;Ysebaert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, most of these changes were related to few dominant species that were abundant only in some periods, such as M. subpictus and the non-indigenous P. emertoni in winter, which are associated with vegetated habitats, or to the strong reduction of the species richness in summer. A maximum of abundance and species richness values have been found in colder regions at the end of the summer and in autumn (Ibañez & Dauvin, 1988;Gestoso et al, 2007;Moreira et al, 2010), as a result of recruitment events occurring in spring and summer. In the Mediterranean, maxima are observed usually in spring and summer (Koulouri et al, 2006;Rueda et al, 2001;Sardà et al, 1999), in agreement with our own observations at La Goulette.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we recorded a 0.47% dominance value of J. striatus. Recently, Moreira et al, (2010) reported 4 species of Rissoidae and Trochidae in subtidal sandy sediments of Iberian Peninsula. In this study, we recorded 5 species from Trochidae and 4 species from Rissoidae.…”
Section: Discussionmentioning
confidence: 99%